(untitled) (Bangladesh Critical Care Journal, 2026)
Background: Tubercular pleural effusion (TPE) typically presents as unilateral exudative effusion. Bilateral involvement is uncommon and may delay diagnosis, particularly when pleural fluid microbiological tests such as GeneXpert MTB/RIF are negative. Case Presentation: We reported the case of a 29-year-old male who presented with a one-month history of low-grade intermittent fever, shortness of breath, and a dry cough. He had a history of childhood asthma and was a non-smoker. There were no constitutional symptoms or any family history of TB. Chest radiography revealed mild bilateral pleural effusions. Two weeks prior, he had been admitted to a local primary care center in Malaysia and treated for atypical pneumonia. He also reported vague abdominal pain and was diagnosed with GERD and pangastritis. CT-thorax revealed moderate right pleural effusion with patchy alveolar opacities in the left apicoposterior segment of the left upper lobe and subcentimeter mediastinal lymphadenopathy without a tree-in-bud appearance. CT abdomen/pelvis revealed moderate ascites and small bowel wall thickening. A repeat CT thorax 2 weeks later demonstrated increasing right pleural effusion and minimal left pleural effusion, patchy ground glass changes in both upper, right middle, and both lower lobes along with mediastinal lymphadenopathy. Flexible bronchoscopy and medical thoracoscopy were performed. Bronchoalveolar lavage (BAL) and Pleural fluid MTB PCR and Gene Xpert were negative. Medical thoracoscopy revealed classical sago-like pleural nodules. A targeted pleural biopsy revealed caseating granulomatous inflammation that was consistent with tuberculosis. Conclusion: This case highlights that pleural tuberculosis can present atypically, with bilateral effusion and a negative pleural fluid GeneXpert result. In such scenario, medical thoracoscopy remains the diagnostic cornerstone for early and definitive diagnosis. Bangladesh Crit Care J March 2026; 14 (1): 55-58